Evaluation of fertility and teratogenicity of the anthocyanin-rich standardized extract of hibiscus sabdariffa L. loaded niosomes in female sprague dawley rats - Asran, Iffah Izzati Che (2021)
Various medicinal plants including Hibiscus sabdariffa (roselle) are gaining attention in phytotherapy research. Aqueous extract of H. sabdariffa encapsulated in niosome (AEHS-Nio) was formulated to improve the effectiveness of this plant extract. The present study was designed to investigate the possible fertility and teratogenicity of AEHS-Nio in forty female Sprague Dawley rats. The females were administered orally by gavage with AESH-Nio at four different dosages 0 (control), 250, 500 and 1000 mg/kg/day. Treatment began from pre-mating and continued through mating up to the 19th day of pregnancy periods. Throughout this study, the reproductive parameters were evaluated until the day of sacrifice (day 20th of pregnancy). Results obtained revealed no significant differences in general health, behaviours and maternal body weights throughout the treatment period. Furthermore, the mean length of the oestrous cycle was not statistically affected, even though a few rats displayed irregular cycles. In addition, there were no significant differences in the mating and pregnancy indices, the number of corpora lutea and implantation sites, percentages of pre-implantation loss and post-implantation death and reproductive organ weights. Foetal parameters such as the number of live foetuses, sex ratio and body weight were also not statistically affected by AESH-Nio. Ultimately, there were no signs of teratogenicity observed since none of the foetuses exhibited congenital malformations. In conclusion these findings suggest that the oral administration of AEHS-Nio up to 1000 mg/kg/day did not pose any significant toxicity on the fertility and teratogenicity but slightly affect the oestrous cycle in rats.